The pocket universal principles of interior design 100 ways to develop innovative ideas, enhance usability, and design effective solutions - Smith, Kelly Harris; Grimley, Chris (Rockport Publishers, 2024)
The Pocket Universal Principles of Interior Design is a concise visual presentation of 100 fundamental elements of interior design.